Gestão de portfólio de projetos em empresas de varejo: a integração dos portfólios e a institucionalização dos principais atores e elementos - Teixeira, Silvio Cesar Alves (2024)
Project Management is present in different types of companies, but each company has particularities in terms of actors and adoption of methodologies, methods, software, among other elements. This range of actors and elements, such as non-formal project managers, Project Management Offices (PMOs) not recognized by the organization, methods and methodologies not suited to the needs and a range of software adapted for certain functions, employ a complexity to Project Portfolio Management (PPM) especially in retail companies and especially in the integration of Portfolios. That said, this research, arising from a practitioner's field problem, proposes two artifacts for retail companies, these being a model and a method focused on PPM, in line with the objective of the thesis which aims to integrate and institutionalize portfolios of projects, as well as their main actors and elements, driven by the following research question: how to institutionalize and integrate Project Portfolios in retail companies as well as their main actors and elements? To this end, the Design Science Research (DSR) method was used, in order to obtain a solution to this problem with scientific rigor and that can be used by practitioners. The thesis is organized into three studies, with Study 1, through a Systematic Literature Review (RSL) and patent survey, mapping models and methods as well as software discussed in academic literature and patents to identify relevant points to be considered in the proposed artifacts. Study 2, through a new RSL and interviews with Project Managers who work in retail companies, identified the actors and elements present in academic literature and in the field of practitioners, to present a model that supports integration and institutionalization of Project Portfolio in retail companies, and which was the basis for building the next artifact. Study 3 dealt with the construction of the method, which occurred in stages and at each stage, this artifact was demonstrated and validated using action research through the Technical Action Research (TAR) method. As contributions, this thesis brings two artifacts focused on PPM that adhere to the line of innovation research, these being a new model and a new method that can be discussed and evolved in an academic context and that can support practitioners in Project Portfolio Management. retail companies in the management, integration and institutionalization of project portfolios.